2011
DOI: 10.1002/mawe.201100810
|View full text |Cite
|
Sign up to set email alerts
|

Tensile test of lead zirconate titanate (PZT)/Platinum (Pt) thin film

Abstract: This paper presents the results of tensile tests for lead zirconate titanate (PZT)/Platinum (Pt) thin films of 2.15 lm thickness in atmospheric air at room temperature. An axial loading tester developed by the authors was used for the tests. The tester was equipped with a load cell with a maximum capacity of 0.5 N and a non-contact position measuring system based on the principle of capacitance micrometry. Furthermore, the tester was equipped with a CCD (chargecoupled device) system for measuring the displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For example, for 100 𝜇m the ultimate tensile strength is reported to be 238 Mpa. The ultimate stress that we are experiencing in design ( 2) is equal to 13 MPa which is far below the 238 Mpa reported by [35]. Therefore, there will be no fracture in the piezoelectric material due to the applied excitation.…”
Section: Comsol Simulationmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, for 100 𝜇m the ultimate tensile strength is reported to be 238 Mpa. The ultimate stress that we are experiencing in design ( 2) is equal to 13 MPa which is far below the 238 Mpa reported by [35]. Therefore, there will be no fracture in the piezoelectric material due to the applied excitation.…”
Section: Comsol Simulationmentioning
confidence: 65%
“…Thus, it is important to know when the fracture will happen especially when brittle PZTs are used. Park et al [35] investigated this question by studying the tensile strength of PZT thin films. This study reported different ultimate tensile strengths based on the thickness of the film.…”
Section: Comsol Simulationmentioning
confidence: 99%
“…With reference to Figure 8, employing the plane stress modeling, with f = 60 Hz and A = 7:5 kPa, leads to a substantial underestimation of the maximum deformation, thus exposing the device to the possibility of structural failure. By contrast, in this case, the fracture threshold given by Park et al (2011) is exceeded by the 3D model and also by the 2D model with the plane strain assumption.…”
Section: Further Differences Between Plane State Assumptionsmentioning
confidence: 73%
“…A Young's modulus, tensile strength, and maximum elongation for PZT were measured to be 83.8 GPa, 460 MPa, and ~0.5 % respectively. Park et al, investigated the ultimate yield strength of sol-gel spun PZT dog bone tensile samples with varying widths [104]. The total thickness for Park's samples was 2 µm of PZT on top of 0.15 µm of platinum.…”
Section: B Limitations Of Pzt Ceramicsmentioning
confidence: 99%